2019
DOI: 10.1016/j.isci.2019.10.020
|View full text |Cite
|
Sign up to set email alerts
|

MYCN-enhanced Oxidative and Glycolytic Metabolism Reveals Vulnerabilities for Targeting Neuroblastoma

Abstract: SummaryIn pediatric neuroblastoma, MYCN-amplification correlates to poor clinical outcome and new treatment options are needed for these patients. Identifying the metabolic adaptations crucial for tumor progression may be a promising strategy to discover novel therapeutic targets. Here, we have combined proteomics, gene expression profiling, functional analysis, and metabolic tracing to decipher the impact of MYCN on neuroblastoma cell metabolism. We found that high MYCN levels are correlated with altered expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 48 publications
7
63
0
Order By: Relevance
“…In this study, we identify HNF4A as a transcription factor facilitating expression of glycolytic genes HK2 and SLC2A1 in NB. Recent studies indicate that as an oncogene associated with poor survival, MYCN is essential for aerobic glycolysis in NB [31], while the underlying mechanisms remain elusive. We demonstrate that as a MYCN-facilitated lncRNA, HNF4A-AS1 interacts with hnRNPU protein to facilitate transactivation of CTCF, which epigenetically regulates transcription of HNF4A and other genes associated with tumor progression in cis and in trans (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identify HNF4A as a transcription factor facilitating expression of glycolytic genes HK2 and SLC2A1 in NB. Recent studies indicate that as an oncogene associated with poor survival, MYCN is essential for aerobic glycolysis in NB [31], while the underlying mechanisms remain elusive. We demonstrate that as a MYCN-facilitated lncRNA, HNF4A-AS1 interacts with hnRNPU protein to facilitate transactivation of CTCF, which epigenetically regulates transcription of HNF4A and other genes associated with tumor progression in cis and in trans (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MYCN-amplified neuroblastoma cells exhibit enhanced expression of genes and proteins involved in aerobic glycolysis (Warburg effect), oxidative phosphorylation (OXPHOS), detoxification of reactive oxygen species (ROS), and FAO (45). In MYCN-amplified tumor cells, glycolytic enzymes including hexokinase isoform 2 are upregulated, and enzymes associated with the TCA cycle and the electron transport chain, such as citrate synthase and isocitrate dehydrogenase isoform 2, are expressed at high levels.…”
Section: Mitochondrial Metabolic Reprogramming In N-myc-driven Cancermentioning
confidence: 99%
“…In MYCN-amplified tumor cells, glycolytic enzymes including hexokinase isoform 2 are upregulated, and enzymes associated with the TCA cycle and the electron transport chain, such as citrate synthase and isocitrate dehydrogenase isoform 2, are expressed at high levels. Increased expression of N-Myc-induced respiratory subunit genes is correlated with adverse clinical outcome in patients with neuroblastoma (45). A moderate increase in ROS in malignant neoplasms modulates cancer cellular signaling via the oxidation of cysteine.…”
Section: Mitochondrial Metabolic Reprogramming In N-myc-driven Cancermentioning
confidence: 99%
“…While this paper was in review, this was confirmed by results from Oliynyk et al who showed that N-Myc increases the glycolytic and oxidative phosphorylation capacity of MYCN-amplified neuroblastoma cells. Moreover, they could demonstrate glutamine independence of mitochondrial respiration in MYCN-amplified neuroblastoma cells compared with non-MYCN amplified cells and that N-Myc high cells are especially vulnerable to inhibition of fatty acid oxidation 34 . We can conclude from these results that N-Myc reprograms neuroblastoma cells towards a highly energy producing and consuming phenotype.…”
Section: Discussionmentioning
confidence: 99%